Water dynamics in solutions of linear poly (N-isopropyl acrylamide) studied by 2H NMR field-cycling relaxometry - Säckel, Christoph; von Klitzing, Regine; Siegel, Renée; Senker, Jürgen; Vogel, Michael (Frontiers in Soft Matter, 2024)
We use 2 H nuclear magnetic resonance to study the dynamics of deuterated water in a solution of linear poly(N-isopropyl acrylamide) (pNIPAM, 4 wt%) across its coil-to-globule transition at a lower critical solubility temperature (LCST) around 32 • C. In agreement with previous studies, we find that the 2 H spin-lattice (T 1 ) and, in particular, spin-spin (T 2 ) relaxation times abruptly decrease when heating through the LCST, indicating that the polymer collapse causes an emergence of a water fraction with strongly reduced mobility. To quantify the dynamics of this slow water fraction, we exploit the fact that 2 H field-cycling relaxometry allows us to measure the spectral density of the water reorientation in a broad frequency range. We find that the slow water fraction is characterised by a broad logarithmic Gaussian distribution of correlation times (σ LG = 2.3), which is centred about τ LG ≈ 10 -9 s near the LCST. Hence, the common assumption of a Debye spectral density does not apply. We argue that a minor water fraction, which is located inside the pNIPAM globules and shows dynamics governed by the disordered polymer matrix, accompanies a major water fraction with bulk-like dynamics above the LCST. The former fraction amounts to about 0.4 water molecules per NIPAM monomer. Several findings indicate fast exchange between these bound and free water fractions on the T 1 and T 2 time scales.